LAW STUDENT PROJECT: PEMBERDAYAAN KOMUNITAS PELUKIS DAERAH PEJATEN BARAT TERHADAP PERLINDUNGAN HAK CIPTA DAN PENDAFTARAN CIPTAAN SENI LUKIS - Simanjuntak, Anni Alvionita; Fauzan, Muhammad; Saffanah, Arla Haiqa; Reza, Muhammad (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2024)
Community service is one of the pillars of the Tri Dharma of Higher Education which must be implemented. Lecturers and students at the Faculty of Law, National Development University "Veteran" Jakarta collaborated in a community service activity with partners targeting the community around RPRA Malinjo, Pejaten, South Jakarta City. This service activity aims to improve the quality and legal awareness in the community regarding Intellectual Property Rights, especially Copyright. Of course, this service activity is expected to provide significant benefits to the community. In achieving its objectives, this service activity uses the latest and innovative methods, such as collaborating legal counseling methods and community character development methods to achieve the objectives of this work program.